Genetic diversity and selection in three plasmodium vivax merozoite surface protein 7 (pvmsp-7) genes in a colombian population (2012)
A completely effective vaccine for malaria (one of the major infectious diseases worldwide) is not yet available; different membrane proteins involved in parasite-host interactions have been proposed as candidates for designing it. It has been found that proteins encoded by the merozoite surface protein (msp)-7 multigene family are antibody targets in natural infection; the nucleotide diversity of three Pvmsp-7 genes was thus analyzed in a Colombian parasite population. By contrast with P. falciparum msp-7 loci and ancestral P. vivax msp-7 genes, specie-specific duplicates of the latter specie display high genetic variability, generated by single nucleotide polymorphisms, repeat regions, and recombination. At least three major allele types are present in Pvmsp-7C, Pvmsp-7H and Pvmsp-7I and positive selection seems to be operating on the central region of these msp-7 genes. Although this region has high genetic polymorphism, the C-terminus (Pfam domain ID: PF12948) is conserved and could be an important candidate when designing a subunit-based antimalarial vaccine.